2021
DOI: 10.3389/fvets.2021.671330
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Donkey Pain Scale (DOPS) for Assessing Postoperative Pain in Donkeys

Abstract: This study aimed to validate a scale for assessing acute pain in donkeys. Forty-four adult donkeys underwent castration after sedation with intravenous (IV) xylazine, induction with guaifenesin and thiopental IV, local anesthetic block, and maintenance with isoflurane. The scale was constructed from a pilot study with four animals combined with algetic behaviors described for equines. After content validation, the scale was evaluated in 40 other donkeys by three blinded and one reference evaluator, by means of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 60 publications
1
20
1
Order By: Relevance
“…There are different ways to investigate dimensionality and multiple association between variables according to exploratory and/or confirmatory factor analysis. Principal component analysis, an exploratory analysis, was used herein to maintain consistency with previously validated scales in other species [ 15 , 22 25 ]. According to PCA all items pertained to the first dimension, except attention to the affected area, which pertained to the second dimension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are different ways to investigate dimensionality and multiple association between variables according to exploratory and/or confirmatory factor analysis. Principal component analysis, an exploratory analysis, was used herein to maintain consistency with previously validated scales in other species [ 15 , 22 25 ]. According to PCA all items pertained to the first dimension, except attention to the affected area, which pertained to the second dimension.…”
Section: Discussionmentioning
confidence: 99%
“…In other species, behavioural scales designed to assess pain stand out for providing evidence of validity, reliability, and sensitivity [ 21 ] and because they have defined cut-off points, such as that developed for cats [ 15 ], cattle [ 22 ], pigs [ 23 ], sheep [ 24 ], and donkeys [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected for an instrument that measures pain, all items’ eigenvectors were pointed to the moments of pain (after surgery and 24 h) and in the opposite direction to moments cats were supposedly pain-free (before surgery) or experiencing mild pain (after rescue analgesia). According to the Kaiser criterion, one component was selected, hence UFEPS-SF is unidimensional ( Streiner, Norman & Cairney, 2015 ) as reported for other pain scales in cattle ( de Oliveira et al, 2014 ), pigs ( Luna et al, 2020 ), sheep ( Silva et al, 2020 ), horses ( Taffarel et al, 2015 ; Barreto da Rocha et al, 2021 ) and donkeys ( de Oliveira et al, 2021 ). The only statistically defined multidimensional animal pain scale in cats is UFEPS ( Brondani et al, 2013b ); however, this classification is based on multivariate analysis and not on biological terms.…”
Section: Discussionmentioning
confidence: 99%
“…UFEPS was chosen as one of the ‘gold standard’ instruments since it has undergone a robust validity protocol ( Merola & Mills, 2016 ). However, as UFEPS-SF was derived from UFEPS, the CPMS-Feline was also used for comparison ( Reid et al, 2017 ), and so were the unidimensional scales, as previously reported in cats and other species ( Barreto da Rocha et al, 2021 ; Brondani et al, 2013b ; Luna et al, 2020 ; de Oliveira et al, 2014 ; Taffarel et al, 2015 ; Silva et al, 2020 ; de Oliveira et al, 2021 ). The correlations equal to or above 0.9 in all comparisons confirmed concurrent criterion validity.…”
Section: Discussionmentioning
confidence: 99%